2001
DOI: 10.2337/diabetes.50.4.891
|View full text |Cite
|
Sign up to set email alerts
|

The Pro12→Ala Substitution in PPAR-γ Is Associated With Resistance to Development of Diabetes in the General Population

Abstract: The allele frequencies for a Pro 12 3 Ala substitution in peroxisome proliferator-activated receptor-␥ differ among ethnic groups, and its relationship with diabetes and associated diseases is controversial. The prevalence of this polymorphism and its effects on clinical characteristics have now been evaluated with a large number of Japanese individuals with type 2 diabetes (n ‫؍‬ 2,201) and normal control subjects (n ‫؍‬ 1,212) recruited by 10 institutions located in seven different cities in Japan. The allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
131
6
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(170 citation statements)
references
References 16 publications
26
131
6
7
Order By: Relevance
“…This Pro 12 Ala SNP has been associated with reduced transcriptional activity in vitro [17]. Discordant results have been reported in the literature [17][18][19][20][21][22][23]; however, a recent meta-analyses of 16 studies, which included over 3,000 individuals, demonstrated that the Ala allele confers protection from diabetes (21% risk reduction) [24,25]. It is possible that the environment, particularly diet or exercise habits, could modify the genotype effect and may account for a portion of the disparity found between separate studies.…”
Section: Introductionsupporting
confidence: 82%
“…This Pro 12 Ala SNP has been associated with reduced transcriptional activity in vitro [17]. Discordant results have been reported in the literature [17][18][19][20][21][22][23]; however, a recent meta-analyses of 16 studies, which included over 3,000 individuals, demonstrated that the Ala allele confers protection from diabetes (21% risk reduction) [24,25]. It is possible that the environment, particularly diet or exercise habits, could modify the genotype effect and may account for a portion of the disparity found between separate studies.…”
Section: Introductionsupporting
confidence: 82%
“…The 12Ala allele was associated with a higher reduction in the 2-h serum insulin level, probably indicating an increase in insulin sensitivity. However, it cannot be excluded that a decrease in insulin levels could also be due to impaired insulin secretion, because the 12Ala allele has been associated with reduced insulin secretion capacity in previous studies [20,47].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the PPAR-γ gene has been viewed as a "thrifty gene", with an important role in the development of type 2 diabetes and diabetes-related traits [7,15]. Additionally, the Pro12Ala substitution in exon B of the PPAR-γ2 gene, first reported in Caucasians [16], has been associated with diabetes mellitus [17,18,19,20,21,22,23,24,25,26,27,28]. Although not all associations have been consistent, a meta-analysis of published studies has confirmed a modest (1.25-fold), but statistically significant, increase in diabetes risk for the Pro12Pro genotype [4,19].…”
Section: Introductionmentioning
confidence: 99%
“…All study subjects (n=549) were Japanese, unrelated and gave their written informed consent to participate in the study for the identification of Type II diabetes genes in Japan [23,24] [25]. The healthy control subjects were selected according to the following criteria: no past history of urinary sugar or of glucose intolerance, an HbA 1c level of less than 5.6%, an age of older than 60 years, and no family history of diabetes mellitus.…”
Section: Ultraviolet (Uv)-induced Cross-linkingmentioning
confidence: 99%
“…The healthy control subjects were selected according to the following criteria: no past history of urinary sugar or of glucose intolerance, an HbA 1c level of less than 5.6%, an age of older than 60 years, and no family history of diabetes mellitus. These criteria which could enhance statistical power to detect associations were also used in previous reports from our laboratory [23,24]. The investigation was carried out in accordance with the guidelines expressed in the Declaration of Helsinki.…”
Section: Ultraviolet (Uv)-induced Cross-linkingmentioning
confidence: 99%